Human systems integration of agricultural machinery in developing economy countries: Sudan as a case study - Ahmed, Hamza, author; Miller, Erika, advisor; Owiny, James, committee member; Simske, Steve, committee member; Jablonski, Becca, committee member; Herber, Daniel, committee member (Colorado State University. Libraries, 2022)
Widespread adoption of agricultural machinery for developing economy countries is commonly regarded as a fundamental component of pro-poor growth and sustainable intensification. Mechanized farming can also improve perceptions of farming and mitigate rural-out migration. However, many traditional farmers do not have access to machinery and/or the machinery is cost prohibitive. This study applies the systems engineering approach to identify human-systems integration (HSI) solutions in agricultural practices to more effectively adapt technologies to satisfy traditional farmers' needs. A treatment control study was conducted on 36 farms in Sudan, Africa, over three farming seasons: 2019 (baseline), 2020, and 2021. The treatment group farmers (N = 6) were provided with agricultural machinery (i.e., tractor, cultivator, planter, and harvester), fuel for the machinery, and training to use the machinery. Farmers were interviewed at the beginning of the study and then after each planting and harvesting season during the study. Findings show that the most significant barriers for technology adoption were culture, security, and maintenance costs. However, they also reported that the most significant challenges in their nonmechanized farming practices were related to labor, safety, and profit margins, all of which could be addressed with machinery. Moreover, the results show that all farmers had similar net profits in 2019, when farming without machinery, while mechanized farming yielded significantly higher net profits ($16.61 per acre more in 2020 and $27.10 per acre more in 2021). Farmers also provided needs and rationales of various design options in tractors and attachments. The findings of this dissertation suggest that, despite the initial resistance to using agricultural machinery, the farmers were pleased by their experience after using farming machinery and expressed an even more accepting attitude from their children towards this new farming process. These results demonstrate the importance of developing effective solutions for integrating farming technology into rural farming practices in developing economy countries. More broadly, this study can be used as an HSI framework for identifying design needs and integrating technology into users' lifestyle. The results presented in this dissertation provide a quantified difference between farming with and without machinery, which can provide a financial basis for purchasing and borrowing models, machinery design requirements, and educational value to farmers. Further, the financial values and design requirements can help inform farmers regarding expected costs, returns, and payoffs from tractor adoption. Manufacturers and policymakers can utilize this to promote technology adoption more effectively to farmers in developing economy countries.